2019
DOI: 10.21511/ppm.17(2).2019.17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethical leadership on management accountants’ performance: the mediating role of psychological well-being

Abstract: This paper examined the impacts imparted by ethical leadership on both the performance and well-being of management accountants employed in public shareholding companies operating in Jordan. The mediating effect of psychological well-being was also examined. In testing the study hypotheses, analysis was performed on 93 obtained responses. The structural equation modeling (SEM) approach was used. From the outcomes, the ethical leadership level has significant impact on the psychological well-being of management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
5
0
1
Order By: Relevance
“…The test checks the strength of the structural path in determining the goodness-of-fit of the proposed business adoption of the cashless payment systems model. The standardized root means that the square residual (SRMR) value required in determining the goodness-of-fit for both measurement and structural model should be less than 0.0813 [77]. This study's SRMR value for the measurement is 0.074, and the structural model is 0.080.…”
Section: Structural Model Analysismentioning
confidence: 81%
See 2 more Smart Citations
“…The test checks the strength of the structural path in determining the goodness-of-fit of the proposed business adoption of the cashless payment systems model. The standardized root means that the square residual (SRMR) value required in determining the goodness-of-fit for both measurement and structural model should be less than 0.0813 [77]. This study's SRMR value for the measurement is 0.074, and the structural model is 0.080.…”
Section: Structural Model Analysismentioning
confidence: 81%
“…Following Hair et al [74], we have observed indicators of a good fit of the model, such as predictive relevance (Q 2 ), path coefficient (β), and their coefficient of determination (R 2 ) or confidence intervals for the evaluation of the structural model. The Q-square values higher than 0.35 indicate that the exogenous variable has strong predictive relevance for a given endogenous variable [77]. Table 4 showed the predictive relevance of Stone-Geisser's Q 2 value [78] The findings revealed that the structural model has a Q-square threshold between 0.065 and 0.521, indicating good results.…”
Section: Structural Model Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Third, individual-level job-related affective well-being partially mediates the relationship between group-level ethical leadership and individual-level OCB. Previous studies have determined that ethical leadership can positively promote employee's wellbeing [59,88]. However, studies on the affective well-being of millennials and how affective well-being can promote OCB are limited [89].…”
Section: Discussionmentioning
confidence: 99%
“…Kalshoven and Boon [92] found that employees with poor well-being may be less productive, make lower-quality decisions, and be absent from work more frequently. Therefore, for organizations, focusing on improving employee wellbeing seems important [88]. According to this research, millennials respond well to ethical leadership; therefore, organizations could use ethical leadership, such as power-sharing, caring, and fairness, to enhance employee well-being.…”
Section: Practical Implicationsmentioning
confidence: 90%